Periodic Visuotactile Stimulation Slowly Enhances the Rubber Hand Illusion in Individuals with High Autistic Traits - Ide, Masakazu; Wada, Makoto (Frontiers in Integrative Neuroscience, 2016)
In a rubber hand illusion (RHI) task, synchronous brush stroking of a rubber hand and a participant's hidden hand induces body ownership of the rubber hand. The effects of spatial distances and temporal lags on the RHI have been extensively examined; however, the effect of periodicity of the stimuli on illusory body ownership has not been examined. Meanwhile, the occurrence of RHI tends to be weak in individuals with autism-spectrum disorders (ASD) and high autistic traits. Preference for stimulus having regularity of tempo is generally observed in individuals with ASD, and thus, periodic stimulation might be more effective to elicit the body ownership illusion in individuals with high autistic traits. Hence, we investigated whether stimulus periodicity influenced RHI as well as its association with participant's autistic traits. Brush strokes were applied to a participant's own hand and the rubber hand periodically (2 s) or non-periodically (1–3 s), either synchronously or asynchronously. Two blocks were performed in each condition. We found that periodic stimulation enhanced the spatial updating of tactile sensation induced by RHI in the subsequent block in participants with high autistic traits, whereas both periodic and non-periodic stimulation strongly elicited RHI in blocks 1 and 2. These results indicate that the periodicity of stimulation has different effects based on an individual's autistic traits. Since individuals with ASD are known to sustain their focus on interoceptive sensations (heartbeats), a periodic stimulation that is potentially correlated with heartbeats might be effective to enhance the visuotactile integration during RHI in individuals with high autistic traits.